Zur kommerziellen Normalisierung illegaler Migration: Akteure in der Agrarindustrie von Almería, Spanien - Hoffmann, Felix (transcript, 2017)
Earn your legality? Thousands of »illegal aliens« are slaving away in the hothouse industry of Almería, hoping for legitimization and a »normal« way of life.